(untitled) (Eurasian Medical Research Periodical, 2025)
The fragmented and inefficient healthcare system in the United States leads to many preventable deaths and unnecessary costs every year. Universal healthcare could have alleviated the mortality caused by a confluence of negative COVID-related factors. Incorporating the demography of the uninsured with age-specific COVID-19 and nonpandemic mortality, we estimated that a single-payer universal healthcare system would have saved 212,000 lives in 2020 alone. We also calculated that US105.6 billion of medical expenses associated with COVID-19 hospitalization could have been averted by a Medicare for All system